Intelligent Paddy Disease Diagnosis System Using Case-Based Reasoning - Hasnatul Nazuha, Hassan (2004)

(untitled)
Case-based reasoning (CBR) ia a recent approach to problem solving and learning that has got a lot of attention over the last few years. Case-based is an innovative technology that enables the implementation of 'intelligent' functions in embedded systems. It has been implemented in different kind of domain and area. In this study, we will look at the development and design of intelligent paddy disease diagnosis system using case-based reasoning technique.